Erzeugen Einkaufzentren Verkehr? Eine Bewertung des Einkaufsverkehrs am Beispiel nicht-integrierter Einkaufszentren im Großraum Innsbruck - Borsdorf, Axel; Schöffthaler, Gerhard (ERDKUNDE, 2000)
Investigations concerning the influence of non-integrated shopping-centers on urban traffic often yield results that are unique for each urban area, so that they should not be generalized. Planning procedures that in many cases lead to the installation of new shopping centers are often oriented only to the specific location and rarely consider broader implications. On the other hand scientists who utilize spatial analyses are frequently critical of such procedures when they lead to the proposed development of peripherical malls. This investigation proves that only the combination of locational and spatial analyses provide reliable information for addressing the impact of shopping center development on traffic flow. We demonstrate that the induction of traffic to the Innsbruck shopping centers is significally less than it was previously assumed. In addition the diversion of consumers from the sensible traffic areas of the downtown core is considerable. Two scenarios were calculated in order to compare the results with a hypothetical situation that assumes Innsbruck’s two peripherical malls do not exist. The results of the two scenarios illustrate impressively that without the peripherical malls, traffic would overwhelm the capacity of the inner-urban traffic system.